Sanitary ceramic and preparation method thereof
By using a glaze layer process combining modified silicon carbide whiskers and specific raw materials, the problems of easy wear and contaminant accumulation in sanitary ceramics have been solved, achieving smooth, antibacterial, and stain-resistant ceramic surfaces, extending service life, and reducing production costs.
Patent Information
- Application Number
- CN202411557501.X
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-11-04
- Publication Date
- 2025-01-07
AI Technical Summary
Existing sanitary ceramics are prone to wear and tear, reduced gloss, and fading color during use, and they easily accumulate pollutants, resulting in a shortened service life. Current technologies increase production costs and have poor stain resistance.
A glaze layer is prepared by using modified silicon carbide whiskers and a specific ratio of raw materials such as feldspar, quartz, calcite, dolomite, zirconium silicate, zinc oxide, and alumina through a spray glazing process. The surface of the modified silicon carbide whiskers is coated with TiO2 micro-nano structures, which improves the toughness, hardness, and antibacterial properties of the glaze.
The prepared sanitary ceramics have a smooth and glossy surface, good anti-fouling and antibacterial effects, extend service life, reduce dirt deposition, meet consumer needs, and the process is environmentally friendly and low-cost.
Smart Images

Figure BDA0005116922040000091
Abstract
Description
Technical Field
[0001] The invention belongs to the technical field of ceramics, and in particular relates to sanitary ceramics and a preparation method thereof. Background Art
[0002] Sanitary ceramics are indispensable sanitary equipment in modern families. Most sanitary ceramics are made of kaolin, quartz and other raw materials. There are many types of sanitary ceramic products. According to their different functions, they can be divided into toilets, wash basins, bathtubs, etc. In the production process, sanitary ceramics are usually made of clay, feldspar and quartz as the main raw materials, and are made through mixing, molding and high-temperature firing. The production process includes steps such as slip casting, drying, glaze treatment and calcination.
[0003] In recent years, with the improvement of consumer demand and consumption level, not only the surface smoothness and aesthetic effect of sanitary ceramic products are required to be higher, but also the use characteristics of the products are required to be higher. However, sanitary ceramics are different from decorative porcelain. They are often washed and worn during use, and the aging phenomenon is obvious, which causes the gloss of sanitary ceramics to decrease and the color to fade, seriously shortening the service life of sanitary ceramics. The quality of sanitary ceramics is most critical to the glaze layer, and the composition of the glaze has a great influence on the performance of the glaze layer. Therefore, it is very important to improve the wear resistance of sanitary ceramics by improving the ceramic glaze. At the same time, some pollutants that ceramic products come into contact with during use, such as scale, soap foam, fatty acids, etc., are easily accumulated on the concave and convex parts of the product surface or enter the micropores under the action of various physical or chemical forces such as van der Waals force, capillary force, hydrogen bond, etc., causing pollution of sanitary ceramic products. The Chinese patent application document with patent application number CN 103102175 A discloses a self-cleaning glaze for sanitary ware, which enhances the anti-fouling property by applying the self-cleaning glaze on the outer layer of the opalescent glaze. This method increases the production process and production cost, and has no inhibitory effect on the formation of scale. The formation of the scale layer will make the anti-fouling property worse and worse. Therefore, how to develop a high-performance sanitary ceramic is a technical problem that needs to be solved urgently. Summary of the invention
[0004] The object of the present invention is to provide a sanitary ceramic and a preparation method thereof to solve one of the technical problems mentioned in the background technology.
[0005] The purpose of the present invention can be achieved through the following technical solutions:
[0006] The first aspect of the present invention provides a sanitary ceramic, comprising a ceramic body and a glaze layer, wherein the glaze layer comprises the following raw materials in parts by weight:
[0007] 30-35 parts of feldspar, 23-26 parts of quartz, 10-15 parts of calcite, 5-8 parts of dolomite, 6-9 parts of zirconium silicate, 3-6 parts of zinc oxide, 2-3 parts of aluminum oxide, 1-3 parts of frit, 0.5-2 parts of modified silicon carbide whiskers, and 0.05-0.1 parts of dispersing aid.
[0008] As a further embodiment of the present invention, the modified silicon carbide whisker is prepared by the following steps:
[0009] Titanium sulfate and urea are added to distilled water, ultrasonically dispersed, and silicon carbide whiskers are added and soaked for 20-30 hours. After being taken out, they are dried at room temperature, vacuum dried, and finally sintered to obtain modified silicon carbide whiskers. A TiO2 micro-nanostructure functional layer is constructed on the surface of silicon carbide whiskers by in-situ deposition of a mixed solution of urea and titanium sulfate combined with low-temperature calcination. The dispersion performance of silicon carbide whiskers is improved, and the titanium dioxide generated on the surface has excellent antibacterial properties. The modified silicon carbide crystals are introduced into the glaze raw materials, which not only improves the toughness and hardness of the glaze, but also enhances the wear resistance and antibacterial properties of the glaze.
[0010] As a further embodiment of the present invention, the usage ratio of titanium sulfate, urea, distilled water and silicon carbide whiskers is 4.8-5.0 g: 2.4-2.5 g: 100 mL: 5.5-6.0 g.
[0011] As a further solution of the present invention, the sintering temperature in the sintering process is 900-950°C, the heating rate is 3-4°C / min, and the heat preservation time is 2-2.5h.
[0012] As a further embodiment of the present invention, the feldspar is at least one of albite and potassium feldspar.
[0013] As a further solution of the present invention, the particle size of the zirconium silicate is 1.0-1.35 μm. The finer the zirconium silicate, the lower the high temperature viscosity and the better the opacifying effect, so the covering ability is strong; adding zirconium silicate can improve the chemical stability, wear resistance and alkali resistance of the glaze.
[0014] As a further solution of the present invention, the particle size of the quartz is 35-45 μm.
[0015] As a further embodiment of the present invention, the dispersing aid is one of sodium polycarboxylate, sodium metasilicate, ammonium polyacrylate, sodium polyacrylate and sodium hexametaphosphate.
[0016] A second aspect of the present invention provides a method for preparing sanitary ceramics, comprising the following steps:
[0017] Step 1, preparing a sanitary ceramic body;
[0018] Step 2, pre-ball-milling the frit according to weight, then adding feldspar, quartz, calcite, dolomite, zirconium silicate, zinc oxide, aluminum oxide, modified silicon carbide whisker and dispersing aid to mix, adding water to continue ball-milling, then performing primary iron removal and screening, secondary iron removal and screening to obtain glaze slurry;
[0019] Step 3, using a glaze spraying method to evenly spray the glaze slurry obtained in step 2 on the sanitary ceramic body obtained in step 1 to obtain a glazed body;
[0020] Step 4: glaze-fire the glazed body obtained in step 3 to obtain sanitary ceramics.
[0021] As a further solution of the present invention, the amount of water added in step 2 is 40-50wt% of the glaze; the mesh size in the first iron removal screening in step 2 is 160-180 mesh, and the mesh size in the second iron removal screening is 200-250 mesh.
[0022] Beneficial effects of the present invention:
[0023] 1) The present invention provides a sanitary ceramic, which is made of feldspar, quartz, calcite, dolomite, zirconium silicate, zinc oxide, aluminum oxide, frit, modified silicon carbide whiskers and dispersing aids as raw materials, which are then mixed to prepare a glaze, and then evenly coated on a ceramic body and sintered to prepare a finished sanitary ceramic. The obtained sanitary ceramic has a smooth and shiny appearance and has good anti-fouling and antibacterial effects.
[0024] 2) The calcite and dolomite added to the raw material components of the glaze layer of the present invention mainly play a role in fluxing. The magnesium carbonate contained in dolomite helps to widen the sintering temperature. The appropriate amount of dolomite can play a role in regulating the calcium and magnesium content, thereby adjusting the high-temperature viscosity and surface tension of the glaze melt. And the proportion of quartz is appropriately increased to increase the content of SiO2, so that the viscosity of the glaze at the highest firing temperature is appropriate, so that the glaze can be spread evenly on the surface of the body, thereby reducing the pits on the glaze surface, thereby effectively inhibiting the formation of scale and preventing dirt deposition. Further, the modified silicon carbide whisker has a very high hardness and a certain toughness, so it can significantly improve the shortcomings of ceramic glaze brittleness, wear resistance, etc. At the same time, the titanium dioxide coated on its surface also has + excellent antibacterial properties, thereby improving the antibacterial properties of sanitary ceramics, reducing the situation where bacteria on the surface of sanitary ceramics affect human health, and extending the service life of sanitary ceramics.
[0025] 3) The preparation method of the sanitary ceramics provided by the present invention greatly reduces the pollution to the environment. At the same time, the process conditions are mild. The obtained sanitary ceramics have a delicate surface and bright color, and have certain antibacterial properties, which meets the needs of consumers and has good practicality and promotion. DETAILED DESCRIPTION
[0026] The following will be combined with the embodiments of the present invention to clearly and completely describe the technical solutions in the embodiments of the present invention. Obviously, the described embodiments are only part of the embodiments of the present invention, not all of the embodiments. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection of the present invention.
[0027] Example 1
[0028] This embodiment provides a sanitary ceramic, including a ceramic body and a glaze layer, wherein the glaze layer includes the following raw materials in parts by weight:
[0029] 30 parts of albite, 25 parts of quartz (35μm), 12 parts of calcite, 5 parts of dolomite, 6 parts of zirconium silicate (1.0μm), 3 parts of zinc oxide, 2 parts of aluminum oxide, 2 parts of frit, 0.55 parts of modified silicon carbide whiskers, and 0.05 parts of sodium polycarboxylate.
[0030] The preparation method of modified silicon carbide whiskers is as follows:
[0031] Add 4.8g titanium sulfate and 2.4g urea to 100mL distilled water, ultrasonically disperse, add 5.5g silicon carbide whiskers, soak for 20h, take out and dry at room temperature, then place in a vacuum drying oven at 80°C for 30min, and finally place in a muffle furnace for sintering at a sintering temperature of 900°C, a heating rate of 3°C / min, and keep warm for 2h to obtain modified silicon carbide whiskers.
[0032] The preparation method of the sanitary ceramics comprises the following steps:
[0033] Step 1, preparing a sanitary ceramic body;
[0034] Step 2, pre-ball-milling the frit according to weight, then adding feldspar, quartz, calcite, dolomite, zirconium silicate, zinc oxide, aluminum oxide, modified silicon carbide whisker and sodium polycarboxylate to mix, and adding 40wt% of water of the glaze to continue ball-milling, and then removing iron once and passing through a 160-mesh sieve, and removing iron twice and passing through a 200-mesh sieve to obtain a glaze slurry;
[0035] Step 3, using a glaze spraying method to evenly spray the glaze slurry obtained in step 2 on the sanitary ceramic body obtained in step 1 to obtain a glazed body;
[0036] Step 4: glaze-fire the glazed body obtained in step 3 to obtain sanitary ceramics.
[0037] Example 2
[0038] Compared with Example 1, the only difference is:
[0039] The preparation method of modified silicon carbide whiskers is as follows:
[0040] Add 5.0g titanium sulfate and 2.5g urea into 100mL distilled water, disperse ultrasonically, add 6.0g silicon carbide whiskers, soak for 20h, take out and dry at room temperature, then place in a vacuum drying oven at 80°C for 40min, and finally place in a muffle furnace for sintering at a sintering temperature of 900°C, a heating rate of 3°C / min, and keep warm for 2.5h to obtain modified silicon carbide whiskers.
[0041] Example 3
[0042] Compared with Example 1, the only difference is:
[0043] 0.55 parts of modified silicon carbide whiskers were replaced with 1.25 parts of modified silicon carbide whiskers.
[0044] Example 4
[0045] Compared with Example 1, the only difference is:
[0046] 0.55 parts of modified silicon carbide whiskers were replaced with 1.95 parts of modified silicon carbide whiskers.
[0047] Example 5
[0048] Compared with Example 1, the only difference is:
[0049] A sanitary ceramic comprises a ceramic body and a glaze layer, wherein the glaze layer comprises the following raw materials in parts by weight:
[0050] 35 parts of albite, 26 parts of quartz (35μm), 14 parts of calcite, 8 parts of dolomite, 8 parts of zirconium silicate (1.0μm), 4 parts of zinc oxide, 3 parts of aluminum oxide, 1 part of frit, 1.5 parts of modified silicon carbide whiskers, and 0.08 parts of sodium polycarboxylate.
[0051] Example 6
[0052] Compared with Example 1, the only difference is:
[0053] A sanitary ceramic comprises a ceramic body and a glaze layer, wherein the glaze layer comprises the following raw materials in parts by weight:
[0054] 32 parts of albite, 24 parts of quartz (42μm), 13 parts of calcite, 7 parts of dolomite, 6 parts of zirconium silicate (1.15μm), 3 parts of zinc oxide, 3 parts of aluminum oxide, 3 parts of frit, 1 part of modified silicon carbide whisker, and 0.08 parts of sodium polycarboxylate.
[0055] Example 7
[0056] Compared with Example 1, the only difference is:
[0057] Step 2: ball-mill the frit in advance according to weight, then add feldspar, quartz, calcite, dolomite, zirconium silicate, zinc oxide, aluminum oxide, modified silicon carbide whisker and sodium polycarboxylate to mix, and add 50wt% of water of the glaze to continue ball-milling, then remove iron once and pass through a 160-mesh sieve, and remove iron twice and pass through a 200-mesh sieve to obtain a glaze slurry.
[0058] Example 8
[0059] Compared with Example 1, the only difference is:
[0060] Step 2: ball-mill the frit in advance according to weight, then add feldspar, quartz, calcite, dolomite, zirconium silicate, zinc oxide, aluminum oxide, modified silicon carbide whisker and sodium polycarboxylate to mix, and add 40wt% of water of the glaze to continue ball-milling, then remove iron once and pass through a 180-mesh sieve, and remove iron twice and pass through a 250-mesh sieve to obtain a glaze slurry.
[0061] Comparative Example 1
[0062] This comparative example provides a sanitary ceramic, including a ceramic body and a glaze layer, wherein the glaze layer includes the following raw materials in parts by weight:
[0063] 30 parts of albite, 25 parts of quartz (35 μm), 12 parts of calcite, 5 parts of dolomite, 6 parts of zirconium silicate (1.0 μm), 3 parts of zinc oxide, 2 parts of aluminum oxide, 2 parts of frit, and 0.05 parts of sodium polycarboxylate.
[0064] The preparation method of the sanitary ceramics comprises the following steps:
[0065] Step 1, preparing a sanitary ceramic body;
[0066] Step 2, pre-ball-milling the frit according to weight, then adding feldspar, quartz, calcite, dolomite, zirconium silicate, zinc oxide, aluminum oxide and sodium polycarboxylate to mix, and adding 40wt% of water of the glaze to continue ball-milling, and then performing a primary iron removal and passing through a 160-mesh sieve, a secondary iron removal and passing through a 200-mesh sieve to obtain a glaze slurry;
[0067] Step 3, using a glaze spraying method to evenly spray the glaze slurry obtained in step 2 on the sanitary ceramic body obtained in step 1 to obtain a glazed body;
[0068] Step 4: glaze-fire the glazed body obtained in step 3 to obtain sanitary ceramics.
[0069] Comparative Example 2
[0070] Compared with Example 1, the only difference is:
[0071] 0.55 parts of modified silicon carbide whiskers were replaced with 0.35 parts of modified silicon carbide whiskers.
[0072] Comparative Example 3
[0073] Compared with Example 1, the only difference is:
[0074] 0.55 parts of modified silicon carbide whiskers were replaced with 2.15 parts of modified silicon carbide whiskers.
[0075] Comparative Example 4
[0076] Compared with Example 1, the only difference is:
[0077] A sanitary ceramic comprises a ceramic body and a glaze layer, wherein the glaze layer comprises the following raw materials in parts by weight:
[0078] 25 parts of albite, 20 parts of quartz (42μm), 8 parts of calcite, 7 parts of dolomite, 6 parts of zirconium silicate (1.15μm), 3 parts of zinc oxide, 3 parts of aluminum oxide, 3 parts of frit, 1 part of modified silicon carbide whisker, and 0.08 parts of sodium polycarboxylate.
[0079] Comparative Example 5
[0080] Compared with Example 1, the only difference is:
[0081] A sanitary ceramic comprises a ceramic body and a glaze layer, wherein the glaze layer comprises the following raw materials in parts by weight:
[0082] 39 parts of albite, 28 parts of quartz (35μm), 11 parts of calcite, 10 parts of dolomite, 6 parts of zirconium silicate (1.0μm), 4 parts of zinc oxide, 5 parts of aluminum oxide, 1 part of frit, 1.5 parts of modified silicon carbide whiskers, and 0.08 parts of sodium polycarboxylate.
[0083] Comparative Example 6
[0084] Compared with Example 1, the only difference is:
[0085] Step 2: ball-mill the frit in advance according to weight, then add feldspar, quartz, calcite, dolomite, zirconium silicate, zinc oxide, aluminum oxide, modified silicon carbide whisker and sodium polycarboxylate to mix, and add 30wt% of water of the glaze to continue ball-milling, then remove iron once and pass through a 180-mesh sieve, and remove iron twice and pass through a 250-mesh sieve to obtain a glaze slurry.
[0086] Comparative Example 7
[0087] Compared with Example 1, the only difference is:
[0088] Step 2: ball-mill the frit in advance according to weight, then add feldspar, quartz, calcite, dolomite, zirconium silicate, zinc oxide, aluminum oxide, modified silicon carbide whisker and sodium polycarboxylate to mix, and add 40wt% of water of the glaze to continue ball-milling, then remove iron once and pass through a 140-mesh sieve, and remove iron twice and pass through a 170-mesh sieve to obtain a glaze slurry.
[0089] The following performance tests were performed on the sanitary ceramics prepared in Examples 1 to 8 and Comparative Examples 1 to 7:
[0090] 1) Wear resistance and gloss test: The wear resistance and gloss test of the sanitary ceramics prepared in the examples and comparative examples were performed using the method for determining the wear resistance of the glazed tile surface in GB / T 3810.7-2016 Ceramic Tile Test Method.
[0091] 2) Mohs hardness test: Place the high wear-resistant sanitary ceramics steadily on a hard support with the glaze layer facing upwards. Select standard ores with different Mohs values from small to large to scratch the surface of the sample. Use the new edge of the ore to apply force evenly and vertically to scratch the surface of the sample. Note that the force should be moderate. The edge of the standard ore should not be broken due to excessive force to form double or multiple scratch marks. The lowest hardness value that can just produce obvious scratches is taken as the test result.
[0092] 3) Antibacterial property test: The sanitary ceramics prepared in the examples and comparative examples were evenly cleaned 30 times with 84 disinfectant. After cleaning, the antibacterial rate was determined according to the antibacterial property test method.
[0093] 4) Determination of anti-fouling grade: The staining agents used to test the stain resistance of tiles include paste staining agents, staining agents that can undergo oxidation reactions, staining agents that can form thin films, olive oil, etc. The stain resistance is divided into levels 1-5 according to the difficulty of cleaning. The higher the level, the better the stain resistance.
[0094] The above test results are shown in Table 1:
[0095] Table 1
[0096]
[0097] It can be seen from the data in Table 1 that, compared with Comparative Examples 1 to 7, the sanitary ceramics prepared in Examples 1 to 8 have excellent hardness, glossiness, antibacterial properties and antifouling properties. In summary, the sanitary ceramics provided in the present invention have a smooth and glossy appearance, excellent wear resistance, antibacterial properties, and excellent antifouling properties.
[0098] It should be noted that, in this article, relational terms such as first and second, etc. are only used to distinguish one entity or operation from another entity or operation, and do not necessarily require or imply any such actual relationship or order between these entities or operations. Moreover, the terms "include", "comprises" or any other variations thereof are intended to cover non-exclusive inclusion, so that a process, method, article or device including a series of elements includes not only those elements, but also other elements not explicitly listed, or also includes elements inherent to such process, method, article or device.
[0099] Although embodiments of the present invention have been shown and described, it will be appreciated by those skilled in the art that various changes, modifications, substitutions and variations may be made to the embodiments without departing from the principles and spirit of the present invention, and that the scope of the present invention is defined by the appended claims and their equivalents.
Claims
1. A sanitary ceramic, characterized in that: It comprises a ceramic body and a glaze layer, wherein the glaze layer comprises the following raw materials in parts by weight: 30-35 parts of feldspar, 23-26 parts of quartz, 10-15 parts of calcite, 5-8 parts of dolomite, 6-9 parts of zirconium silicate, 3-6 parts of zinc oxide, 2-3 parts of aluminum oxide, 1-3 parts of frit, 0.5-2 parts of modified silicon carbide whiskers, and 0.05-0.1 parts of dispersing aid.
2. A sanitary ceramic according to claim 1, characterized in that: The modified silicon carbide whisker is prepared by the following steps: Titanium sulfate and urea are added into distilled water, ultrasonically dispersed, silicon carbide whiskers are added and soaked for 20-30 hours, taken out and dried at room temperature, vacuum dried, and finally sintered to obtain modified silicon carbide whiskers.
3. A sanitary ceramic according to claim 2, characterized in that: The dosage ratio of titanium sulfate, urea, distilled water and silicon carbide whisker is 4.8-5.0 g: 2.4-2.5 g: 100 mL: 5.5-6.0 g.
4. A sanitary ceramic according to claim 2, characterized in that: The sintering temperature in the sintering process is 900-950° C., the heating rate is 3-4° C. / min, and the heat preservation time is 2-2.5 hours.
5. A sanitary ceramic according to claim 1, characterized in that: The feldspar is at least one of albite and potassium feldspar.
6. A sanitary ceramic according to claim 1, characterized in that: The particle size of the zirconium silicate is 1.0-1.35 μm.
7. A sanitary ceramic according to claim 1, characterized in that: The particle size of the quartz is 35-45 μm.
8. A sanitary ceramic according to claim 1, characterized in that: The dispersing aid is one of sodium polycarboxylate, sodium metasilicate, ammonium polyacrylate, sodium polyacrylate and sodium hexametaphosphate.
9. The method for preparing sanitary ceramics according to claim 1, characterized in that: The following steps are involved: Step 1, preparing a sanitary ceramic body; Step 2, pre-ball-milling the frit according to weight, then adding feldspar, quartz, calcite, dolomite, zirconium silicate, zinc oxide, aluminum oxide, modified silicon carbide whisker and dispersing aid to mix, adding water to continue ball-milling, then performing primary iron removal and screening, secondary iron removal and screening to obtain glaze slurry; Step 3, using a glaze spraying method to evenly spray the glaze slurry obtained in step 2 on the sanitary ceramic body obtained in step 1 to obtain a glazed body; Step 4: glaze-fire the glazed body obtained in step 3 to obtain sanitary ceramics.
10. The method for preparing sanitary ceramics according to claim 9, characterized in that: The amount of water added in step 2 is 40-50wt% of the glaze; the mesh size in the first iron removal screening in step 2 is 160-180 meshes, and the mesh size in the second iron removal screening is 200-250 meshes.
Citation Information
Patent Citations
Self-cleaning glaze and application thereof as well as ceramic sanitary ware
CN103102175A
Glaze capable of increasing brightness and preparation process thereof
CN112340993A
High-hardness digital protective glaze
CN113149437A
Sanitary ceramic and preparation method thereof
CN113149608A
Photocatalyst antibacterial ceramic glaze, preparation method thereof and lightweight ceramic tile
CN113929306A
Cited By
Special ceramic material as well as preparation method and application thereof
CN120004644A